Farming tasks and the development of rheumatoid arthritis in the agricultural health study. Issue 4 (13th February 2019) - Parks, Christine G; Meyer, Armando; Beane Freeman, Laura E; Hofmann, Jonathan N; Sandler, Dale P
Abstract : Objectives: Farming has been associated with rheumatoid arthritis (RA). Some studies have evaluated the effects of pesticides, but other agricultural exposures may also affect immune response. Methods: We investigated non-pesticide agricultural exposures in relation to RA in licensed pesticide applicators (n=27 175, mostly male farmers) and their spouses (n=22 231) in the Agricultural Health Study (AHS) cohort (1993–1997) who completed at least one follow-up survey through 2015. Incident RA cases (n=229 applicators and 249 spouses) were identified based on self-report confirmed by use of disease-modifying antirheumatic drugs or medical records. Hazard Ratios (HRs) and 95% Confidence Intervals (CIs) were estimated by Cox proportional hazard models adjusting for applicator status, state, smoking, education and specific pesticide use, allowing estimates to vary by median age when hazards assumptions were not met. Results: Overall, RA was associated with regularly applying chemical fertilisers (HR=1.50; 95% CI 1.11 to 2.02), using non-gasoline solvents (HR=1.40; 95% CI 1.09 to 1.80), and painting (HR=1.26; 95% CI 1.00 to 1.59). In older applicators (>62 years), RA was associated with driving combines (HR=2.46; 95% CI 1.05 to 5.78) and milking cows (HR=2.56; 95% CI 1.01 to 6.53). In younger participants (≤62 years), RA was inversely associated with raising animals as well as crops (HR=0.68; 95% CI 0.51 to 0.89 vs crops only). Associations with specific crops varied by age: some (eg, hay) were inversely associated with RA in younger participants, while others (eg, alfalfa) were associated with RA in older participants. Conclusion: These findings suggest several agricultural tasks and exposures may contribute to development of RA.